MINIMALISIR KETAKUTAN MASYARAKAT MELALUI SOSIALISASI DAN SIMULASI PEMBERIAN BANTUAN HIDUP DASAR (BHD) - Ferdianto, Ferry; Putra, Sandy Dwiana; Fathiy, Naufal Zahiril; Raissa, Indira (Jurnal Abdimas Bina Bangsa, 2025)
Emergency situations do not only occur due to very dense traffic, but also often occur within the family and community, all of these situations need to be resolved immediately in a matter of minutes or even seconds, so practical knowledge is needed for all people about first aid in emergencies. First aid in emergencies is a series of first efforts that can be done in emergency conditions in order to save patients from death which is better known as Basic Life Support (BLS). BLS socialization and simulation programs are needed to improve community knowledge and skills. This activity is carried out through initial observation, socialization with presentations and demonstrations, and evaluation using pre-tests and post-tests. The evaluation results showed a significant increase in participant understanding, with 42% achieving a good level of understanding after participating in the activity. The supporting factors for the success of this activity were support from village officials and active community participation. Although there were obstacles such as time constraints, this activity provided great benefits in improving community preparedness in emergency situations. With positive results, this education model can be applied in other areas to improve public health literacy.